2017
DOI: 10.1186/s12903-017-0459-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies on core-carrier obturation: a systematic review and meta-analysis

Abstract: BackgroundThis systematic review aimed to evaluate the clinical performance of core-carrier obturation in endodontic treatment.MethodsKeywords of “(core carrier OR Thermafil) OR (cold lateral condensation OR lateral condensation) OR (warm vertical condensation OR vertical condensation) AND (obturation OR root canal filling) AND clinical study” were searched for all obtainable publications up to year 2017 in the databases of PubMed, ScienceDirect, EMBASE, Scopus and Web of Science. The success rate, short-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The presence of the plastic carrier in a Thermafil obturator could make a retreatment and/or the postspace preparation a difficult task. 25 26 What's more, the clinicians who lack the basic principles for use Thermafil obturator could perform a root canal filling with a naked plastic carrier in the last millimeter of the canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the plastic carrier in a Thermafil obturator could make a retreatment and/or the postspace preparation a difficult task. 25 26 What's more, the clinicians who lack the basic principles for use Thermafil obturator could perform a root canal filling with a naked plastic carrier in the last millimeter of the canal.…”
Section: Discussionmentioning
confidence: 99%
“…First, the clinicians, who lack of the basic principles for use Thermafil obturator, could perform a root canal filling with a naked plastic carrier in the last millimeter of the canal. 25 26 Second, the preparation of the postspace, if necessary, in a canal filled with a Thermafil obturator could be very difficult and could cause a postoperative perforation as result of a lack of attention or experience on the part of the clinician. Third, the retreatment management in a tooth filled with a Thermafil obturator could be very difficult for a general practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…In meta-analysis Peng et al 24 investigated outcome of root canal filling with warm gutta-percha (thermomechanical compaction, thermoplasticized injectable gutta-percha obturation, ultrasonic condensation of gutta-percha, and solid-core carry insertion technique) in comparison to cold lateral condensation, and found that incidence of postoperative pain was similar between the two groups, although the overextension was seen more frequent in the former technique. The results of systematic review and metaanalysis of Wong et al 25 indicate that postoperative pain of core-carrier obturation was comparable with that of cold lateral condensation in day 1 and 7 days after intervention. Moreover, no significant difference in the technical quality of root canal filling (overfilling or adequate adaptation) was found between techniques.…”
Section: Obturationmentioning
confidence: 93%
“…15 Obturation techniques that use thermoplasticized gutta-percha have become more frequent because they result in homogeneous fillings and satisfactory sealing against marginal infiltration, 16 but may favor apical extrusion of filling material. 17,18 The filling material when in contact with the periodontal tissues through the apical foramen can potentially modify the healing process in the periodontium 19 and interfere with the occurrence of postoperative pain. 4 The intensity of inflammatory reactions in the apical region depends on several factors, one of these being the composition of the sealer.…”
Section: Introductionmentioning
confidence: 99%